Post-recurrence survival analysis of stage I non-small-cell lung cancer. (November 2017) - Lee, Kanghoon; Kim, Hyeong Ryul; Kim, Dong Kwan; Kim, Yong-Hee; Park, Seung-Ill; Choi, Se Hoon; Han, Junhee
Background: The aim of this retrospective study was to review recurrence patterns of stage I non-small-cell lung cancer and identify prognostic factors for post-recurrence survival. Methods: Among 940 patients with pathological stage I non-small-cell lung cancer who underwent curative resection, 261 experienced a recurrence; of these, 188 had adenocarcinoma and 62 had squamous cell carcinoma. Oligo-recurrence was defined as 1–3 recurrent lesions restricted to a single organ. Potentially curative local treatment included surgery, stereotactic radiotherapy, and photodynamic therapy. Results: The median follow-up duration was 65 months (range 4–186 months). The most common site of recurrence was the lung in 145 patients, followed by mediastinal lymph nodes in 49, pleura in 30, and brain in 27. Local treatment for recurrent tumors included surgery in 59 patients, stereotactic radiotherapy in 46, photodynamic therapy in 2, and other radiotherapy in 41. Seventy-eight patients received chemotherapy only, and 35 received conservative treatment. Among 125 patients who were evaluated for an epidermal growth factor receptor gene mutation, 31 were treated with epidermal growth factor receptor-tyrosine kinase inhibitor. The 3- and 5-year post-recurrence survival rates were 49.1% and 33.8%, respectively. Age at recurrence, adenocarcinoma cell type, disease-free interval, epidermal growth factor receptor-tyrosine kinase inhibitor treatment, and potentially curative local treatment were independent prognostic factors for survival in multivariate analysis. Conclusions: Local treatment for recurrence should be considered in selected candidates, and use of epidermal growth factor receptor-tyrosine kinase inhibitor I is reasonable if an epidermal growth factor receptor mutation is detected.